On the rocketship : - Whitmire, Richard (Jossey-Bass, 2014)
On the Rocketship: How Top Charter Schools are Pushing the Envelope examines the rise and expansion of leading charter school network Rocketship, revealing the "secret sauce" that makes a successful program.